Professional XNA Programming: Building Games for Xbox 360 and Windows with XNA Game Studio 2.0 - Nitschke Benjamin (Wrox, 2008)
This improved and updated edition of the bestseller will get you up and running quickly with building games for Xbox 360 and the Windows platform. Professional game developer and Microsoft MVP Benjamin Nitschke begins by explaining how to install the free XNA Game Studio 2.0 and then goes on to share essential advice for using it in a productive way.